Towards MRI contrast agents responsive to Ca(II) and Mg(II) ions: metal-induced oligomerization of dota-bisphosphonate conjugates - Kubíček, Vojtěch; Vitha, Tomáš; Kotek, Jan; Hermann, Petr; Vander Elst, Luce; Muller, Robert N; Lukeš, Ivan; Peters, Joop A (Contrast media & molecular imaging, 2010)
In magnetic resonance imaging (MRI), paramagnetic complexes are utilized as contrast agents. Much attention has been paid to the development of new contrast agents responsive to pH, temperature or concentration of various components of body liquids. We report a new type of MRI probe sensing the concentrations of calcium and magnesium in biological media. The ligand do3ap(BP) combines a dota-like chelator with a bisphosphonate group. In the complex, the Gd(III) ion is entrapped in the macrocyclic cavity whereas the bisphosphonate group is not coordinated and therefore is available for coordination with endogenous metal ions. In the presence of metal ions, Gd-do3ap(BP) appears to show formation of coordination oligomers leading to an unprecedented increase in r(1) up to 200-500%. The extremely high relaxivity response makes this type of compound interesting for further studies as MRI ion-responsive probes for biomedical research.
Keywords: Magnesium; Diphosphonates; Magnetic Resonance Imaging; hořčík; bisfosfonáty; Calcium; magnetická rezonanční tomografie; kontrastní látky; Contrast Media; gadolinium; vápník; Gadolinium